2003
DOI: 10.1099/mic.0.26334-0
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the polynucleotide phosphorylase gene (pnp) of Streptomyces antibioticus affects mRNA stability and poly(A) tail length but not ppGpp levels

Abstract: The pnp gene, encoding the enzyme polynucleotide phosphorylase (PNPase), was overexpressed in the actinomycin producer Streptomyces antibioticus. Integration of pIJ8600, bearing the thiostrepton-inducible tipA promoter, and its derivatives containing pnp into the S. antibioticus chromosome dramatically increased the growth rate of the resulting strains as compared with the parent strain. Thiostrepton induction of a strain containing pJSE340, bearing pnp with a 5′-flanking region containing an endogenous promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 48 publications
4
33
0
Order By: Relevance
“…4 revealed bands in all three preparations that were 25-35 residues in length. This observation confirms previous results that while oligo(A) stretches of less than 18-20 residues are most commonly observed as components of the heteropolymeric 39-tails of streptomycete RNAs, longer stretches do occur at a lower frequency (Bralley & Jones, 2003). It should be noted that because the poly(A) tails of streptomycete RNAs are highly heteropolymeric (Bralley & Jones, 2002), the pattern of continuous increase in tail length observed in E. coli (lane 3) is not observed for the tails from S. coelicolor.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…4 revealed bands in all three preparations that were 25-35 residues in length. This observation confirms previous results that while oligo(A) stretches of less than 18-20 residues are most commonly observed as components of the heteropolymeric 39-tails of streptomycete RNAs, longer stretches do occur at a lower frequency (Bralley & Jones, 2003). It should be noted that because the poly(A) tails of streptomycete RNAs are highly heteropolymeric (Bralley & Jones, 2002), the pattern of continuous increase in tail length observed in E. coli (lane 3) is not observed for the tails from S. coelicolor.…”
Section: Resultssupporting
confidence: 92%
“…These cDNAs, from leuA (SCO0387), clpP (SCO3044) and a 23S rRNA, were isolated from both wildtype and mutant strains. These clones revealed tails with compositions similar to those previously isolated from genes actII-orf4 and redD (Bralley & Jones, 2002) and S. antibioticus pnp (Bralley & Jones, 2003). The fact that both RNA tail length and composition in the mutant JSE450A appear similar to that found in M145 strongly suggests that RNase PH is not involved in the synthesis of RNA 39-tails in S. coelicolor.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Overexpression of PNPase led to decreased antibiotic production in Streptomyces antibioticus (155). Since the expression of pnp is RNase III dependent in S. coelicolor (156), it will be interesting to investigate the connection of PNPase, RNase III, and antibiotic production.…”
Section: Rna Regulation Of Antibiotic Productionmentioning
confidence: 99%
“…More recently, it has been shown that PNPase also functions as an alternative poly(A) polymerase in E. coli, where under appropriate conditions it can either degrade RNA or synthesize poly(A) tails, also incorporating C and U residues at low frequency in wild-type cells (34). It has further been argued that PNPase serves as perhaps the sole poly(A) polymerase in streptomycetes (7,8), spinach chloroplasts (53), and Synechocystis sp. (46), synthesizing heteropolymeric rather than homopolymeric 3Ј-RNA tails in each of these systems.…”
mentioning
confidence: 99%